Influence of Pt addition to Ni catalysts on the catalytic performance for long term dry reforming of methane - de Miguel, Sergio Ruben (2012)
The influence of Pt addition (in very low concentrations) to a Ni/(10%)/Al 2O 3 catalyst in its catalytic performance during long-term experiments of dry reforming of methane was studied. The monometallic Pt(0.5%)/Al 2O 3 catalyst displayed a pronounced deactivation during 6500 min reaction time, mainly due to a significant sintering of the metallic phase, whereas the monometallic Ni(10%)/Al 2O 3 catalyst showed a high and stable activity along the reaction time. Compared with the Ni(10%)/Al 2O 3 catalyst, the bimetallic Ni(10%)Pt(0.5%)/Al 2O 3 sample showed a higher, and stable catalytic activity during the 6500 min reaction time and a markedly lower carbon deposition. TEM images reveal much less carbon formation and filament grow and this leads to expect a higher stability in long term processes. Characterization techniques indicate that nickel and platinum are in close contact during the simultaneous reduction of the two oxide precursors and that geometric effects (dilution and blocking) are mainly responsible for the excellent catalytic behaviour of the bimetallic NiPt catalyst.